2015
DOI: 10.1038/cr.2015.140
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo pathway effectors YAP and TAZ promote cell growth by modulating amino acid signaling to mTORC1

Abstract: YAP and TAZ are transcriptional co-activators and function as the major effectors of the Hippo tumor suppressor pathway, which controls cell growth, tissue homeostasis, and organ size. Here we show that YAP/TAZ play an essential role in amino acid-induced mTORC1 activation, particularly under nutrient-limiting conditions. Mechanistically, YAP/TAZ act via the TEAD transcription factors to induce expression of the high-affinity leucine transporter LAT1, which is a heterodimeric complex of SLC7A5 and SLC3A2. Dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
168
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(182 citation statements)
references
References 62 publications
14
168
0
Order By: Relevance
“…As a central effector of cell growth and proliferation, mTOR signaling has also been shown to mediate YAP function elsewhere (Hansen et al, 2015; Tumaneng et al, 2012), and our data add to the growing evidence that YAP is able to induce mTOR signaling through several different pathways.…”
Section: Discussionsupporting
confidence: 70%
“…As a central effector of cell growth and proliferation, mTOR signaling has also been shown to mediate YAP function elsewhere (Hansen et al, 2015; Tumaneng et al, 2012), and our data add to the growing evidence that YAP is able to induce mTOR signaling through several different pathways.…”
Section: Discussionsupporting
confidence: 70%
“…This inverse relationship is also clearly evidenced in PC tissues of TCGA dataset. It has been reported that YAP is a transcriptional coactivator and functions as the major effector of the Hippo tumor suppressor pathway, which controls cell growth, tissue homeostasis, and organ size [24]. Inhibition of YAP1 expression greatly reduces detachment-induced apoptosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WNT signaling can stabilize YAP to potentiate its downstream effects, through upregulation of TRIB2, which downregulates a ubiquitin ligase that normally targets YAP for degradation 116 . Additionally, in certain subtypes of HCC, loss of Hippo signaling correlates with mTOR pathway activation 117, 118 , which is thought to proceed through activation of the PI3K pathway via a YAP-induced microRNA that reduces expression of PTEN 119 . YAP has also been shown to activate the mTOR pathway through the upregulation of amino acid transporters, SLC38A1 and SLC7A5 118 .…”
Section: Liver Cancer Developmentmentioning
confidence: 99%